Resilience of Coastal Lake Barriers in Poland in Light of Geological and Bathymetric Data and Hydrodynamic Simulations - Różyński, Grzegorz; Cerkowniak, Grzegorz R. (Frontiers in Marine Science, 2022)
The paper presents a study on the resilience of three coastal lake barriers at the central part of the Polish Baltic Sea coast. It was motivated by recent hi-res geological surveys that had demonstrated for the first time the previously unexpected scale of severe scarcity of sandy sediments there, indicating likely risks of enhanced erosion, breaching and overtopping of the studied barriers. Sediment scarcity will be further exacerbated by climate change, particularly by depletion of ice cover in coastal regions during winters, sea level rise and possible harsher hydrodynamic conditions in general. Evidenced by simulations, the resulting greater energy fluxes attacking sediment hungry coastal barriers regions will certainly produce higher risks of breaching events of the barriers in question. Apart from constant rehabilitation and reinforcement of the dune strip, mitigation of such threats will also necessitate periodic re-nourishments of the outer shoreface region, which should undergo enhanced erosion during future extreme events involving sea level rise conditions. In all, the paper novelty consists in the assessment of aftermaths of future extreme events by combining recent advances in coastal geology and the knowledge on climate change processes. Thus, it demonstrates the need for detailed geological mapping of coastal regions to identify possible future hot spots that under current hydrodynamic conditions show either relatively gentle erosion trends, or are near stability.